Стохастическая полуэмпирическая модель пространственно-временной трансформации современного климата Украины - Бойченко, С.Г.; Волощук, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The structure of analytical stochastic semi-empirical models of the spatio-temporal transformation of a modern regional climate for the plain part of the territory of Ukraine is worked out and proved. By the statistical analysis of the data of instrumental observations on meteorological stations of Ukraine for the period exceeding 100 years, the essential efficiency of these models for the description of climatic fields of the temperature of air and atmospheric precipitations is confirmed.